Searching for new frontiers Hollywood films in the 1960s - Worland, Rick (Hoboken, New Jersey Wiley, 2018)
"This book offers film students and general readers a survey of popular movies of the 1960s. The author explores the most important modes of filmmaking in times that were at once hopeful, exhilarating, and daunting. The text combines discussion of American social and political history and Hollywood industry changes with analysis of some of the era's most expressive movies" --Provided by publisher.
Post Hollywood and a changing America -- Hollywood, Hitchcock, and the postwar era -- Domestic relations, 1953-1967, Bachelor pads, nervous dads, & marriages on the rocks; welcoming The Graduate -- Negotiating the civil rights movement, To kill a mockingbird; the rise of Sidney Poitier -- The new Hollywood, Vietnam, and the schism -- Art cinema and counter-culture, Dr. Strangelove, A Hard day's night, Blow up, Bonnie and Clyde, Weekend -- Nowhere to run: the late western. One-eyed Jacks, The Man who shot Liberty Valance, A Fistful of dollars, the Wild Bunch -- The War, The Longest day, Hell is for heroes, The Dirty dozen, Castle keep, The Green berets -- Far out: new Hollywood voyages of discovery, A Space odyssey, Easy rider.
Includes bibliographical references and index.
Keywords: Motion pictures -- California -- Los Angeles -- History -- 20th century; Motion pictures -- Social aspects -- United States -- History -- 20th century; Motion pictures -- Political aspects -- United States -- History -- 20th century